2019
DOI: 10.3354/meps12901
|View full text |Cite
|
Sign up to set email alerts
|

Diazotroph activity in surface Narragansett Bay sediments in summer is stimulated by hypoxia and organic matter delivery

Abstract: Bacteria that carry out many processes of the nitrogen cycle inhabit estuarine sediments. Denitrification is known to be a dominant process causing estuarine sediments to behave as net nitrogen sinks. However, measurements of nitrogen fluxes in the sediments of Narragansett Bay, Rhode Island, USA, have at times revealed high rates of net nitrogen (N 2 ) fixation. Whereas changes in primary production, in magnitude and phenology, within Narragansett Bay have been identified as possible causes for these changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
(89 reference statements)
3
7
0
Order By: Relevance
“…This may suggest that diazotrophs were associated with chlorophyll‐rich particles that at least partially derive from phytoplankton biomass previously deposited onto the sediments. This is consistent with a previous study in Narragansett Bay sediments showing N 2 fixation stimulated by organic matter inputs (Spinette et al 2019) and the sampling period of the present study coincided with the highest chlorophyll concentrations observed along the year in Narragansett Bay (Oviatt et al 2002). Similar results have been obtained from pelagic tropical and temperate coastal ecosystems, as well as in deep aphotic waters (Moisander et al 2014; Benavides et al 2015; Severin et al 2015).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This may suggest that diazotrophs were associated with chlorophyll‐rich particles that at least partially derive from phytoplankton biomass previously deposited onto the sediments. This is consistent with a previous study in Narragansett Bay sediments showing N 2 fixation stimulated by organic matter inputs (Spinette et al 2019) and the sampling period of the present study coincided with the highest chlorophyll concentrations observed along the year in Narragansett Bay (Oviatt et al 2002). Similar results have been obtained from pelagic tropical and temperate coastal ecosystems, as well as in deep aphotic waters (Moisander et al 2014; Benavides et al 2015; Severin et al 2015).…”
Section: Discussionsupporting
confidence: 94%
“…Many of the dominant diazotrophs observed in the water column during our sampling were affiliated with nifH Subcluster 1A and Cluster III. These sequence clusters contain putative anaerobic diazotrophs previously observed in the Bay's sediments (Fulweiler et al 2013; Brown and Jenkins 2014; Spinette et al 2019) as well as in other temperate and subtropical estuarine systems (Moisander et al 2007; Bentzon‐Tilia et al 2015 b ). The reports of active non‐cyanobacterial diazotrophs in eutrophic coastal and estuarine environments, coupled with molecular evidence of the genetic basis for how heterotrophic bacterial diazotrophs can maintain N 2 fixation under high nitrogen conditions (reviewed in Bombar et al 2016), suggests that eutrophic environments may be a niche for non‐cyanobacterial diazotrophs.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Temperature is another key factor regulating nitrogenase activity (NA) (Sorensen & Michelsen, 2011), and NA has been observed to have a maximum in summer in marine sediments (Bertics et al., 2013). Moreover, other environmental factors, such as the total nitrogen (TN): total phosphorous (TP) molar ratio (Yao et al., 2018), organic matter (Fulweiler et al., 2013; Spinette et al., 2019), and dissolved inorganic nitrogen can also affect BNF (Knapp, 2012).…”
Section: Introductionmentioning
confidence: 99%